Adição de enzimas exógenas na digestibilidade aparente total de rações para leitões na fase de creche - Barros, Pryscilla Cenci de (2010)
The objective of this study to evaluate the effect od addition of amylase and protease, isolated or in combination on the digestibility of nutrients in diets for piglets in the nursery phase. It was used 16 piglets with initial weight of 8.04 kg were individually penned in metabolism cages. The experimental treatments consisted of four isoenergetic and isolisinic and differed only in addiction or not of enzymes: treatment 1 = control diet; treatment 2 = 0.06% of amylase; treatment 3 = 0.0125% of protease; treatment 4 = 0.06% of amylase and 0.0125% of protease. The experimental desing was completely randomized desing with four replications and two phases. No effect of the inclusion of amylase and protease, alone or combined, in the digestibility of dry matter, organic matter, crude protein, ash, starch and gross energy. it is concluded that supplementation with amylase and protease isolated or in combination in diets for piglets in the nursery phase did not result in improvement of digestibility coefficients of the variables, but when nalyzing the phases separately, the digestibility coefficients were higher in the phase 2 in all treatments